An evaluation of Mimorista pulchellalis (Dyar) (Lepidoptera : Pyraustidae) as a biocontrol agent against jointed cactus in South Africa - Nieman, Erik (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1984)
From the introduction: The work on Mimorista is divided into two sections: a laboratory orientated study which describes the biology and rearing techniques and a field orientated study where the establishment of the insect and its impact on jointed cactus populations are examined. In the final chapters the integration of this insect in the current control program are discussed and recommendations regarding its future in South Africa are given.
Keywords: Cactus -- South Africa; Weeds -- Biological control -- South Africa; Pyralidae -- South Africa; Moths -- South Africa